TECHNICAL AND ECONOMIC ANALYSIS OF A PHOTOVOLTAIC SOLAR SYSTEM IN NORTE DE SANTANDER, COLOMBIA - Galvís Villamizar, Dayana Naiyerling; Gomez Camperos, July Andrea; Duque Suárez, Oscar Manuel (Journal of Applied Engineering Science, 2022)
Solar energy is the most abundant renewable resource on the surface of the earth; where through photovoltaic systems electricity is generated using solar cells that work from the incidence of light. The study's objective is to develop technical and economic analysis for installing a photovoltaic solar system in the municipality of El Zulia, Norte de Santander department, Colombia. For this purpose, different studies on this region's solar radiation are taken as a reference, recorded for nine years, and processed using statistical techniques that suggest photovoltaic energy exploitation. Likewise, the electricity consumption averages were obtained and related to the energy rates currently paid by users in this northern region of Santander. Based on this information, the VENSIM model was analyzed to understand the electric microgeneration process in the Colombian residential sector, and the calculations related to the selection of the inverter, the photovoltaic modules, the photovoltaic generator, and other technical specifications were carried out. Finally, the financial evaluation of the photovoltaic solar system was carried out for 25 years, considering the returns on investment from the tax benefits offered by Law 1715 of 2014 and the savings that microgeneration represents for users. Also, the project proved to have financial viability and a payback period of 4 years.
Keywords: solar energy, photovoltaic system, solar panels, financial viability